Differences between pregnant women with secure and fearful attachment patterns with respect to transition to motherhood - Hanak Nataša (Psihološka Istraživanja, 2010)
This study investigated the possibility of discerning differences between attachment patterns of pregnant women in some mental processes during the transition to motherhood. Participants were 335 primiparae, examined between 20 and 32 weeks of pregnancy. The revised version of Questionnaire for Attachment Assessment (UPIPAV-R) was used for the assessment of seven attachment dimensions. Cluster analysis, k means method, was employed for determining the general attachment pattern of the participants. Four clusters were identified: secure, fearful, preoccupied and dismissing. Maternal prenatal attachment, her anxieties about the prospective maternal role and her possibly dysfunctional expectations about the role of the child in her private and family life were assessed using scales developed for the purpose of the research. The hypothesis about differences of attachment patterns in examined mental processes of preparation for motherhood was confirmed by the results of discriminant analysis. All dimensions of maternal prenatal attachment are central for discriminating secure from fearful attachment pattern. All dimensions of possibly dysfunctional expectations are central for discriminating preoccupied from dismissing attachment patterns. Anxiety related to loss of freedom and no self-realization in the mother role has significant contribution to discriminating secure from fearful attachment pattern. The other two dimensions of anxiety, related to the 'difficult baby' and incompetence in mother role, are important for discriminating dismissing from preoccupied attachment patterns. .